(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2026)
Background: Diabetes is a prevalent metabolic disorder linked to increased cardiovascular morbidity and mortality, which cannot be solely attributed to hyperglycemia or conventional cardiovascular risk factors like smoking or hypercholesterolemia. Intensive glycemic control using insulin to achieve near-normal glycemia does not significantly reduce macrovascular complications when compared to conventional glycemic control. The triglyceride glucose index is a significant indicator of the progression from prediabetes to type 2 diabetes mellitus. This study explored the correlation between triglyceride glucose index and HOMA-IR (Homeostatic Model Assessment of Insulin Resistance) in prediabetes group and type 2 diabetes mellitus group. Materials and methods: This Cross-sectional analytical study was carried out in the Department of Biochemistry at Institute of Applied Health Sciences. After conducting non-probability purposive sampling methods 25 prediabetes and 25 type diabetes patients was selected. Fasting blood glucose, fating lipid profile and fasting insulin was measured. The triglyceride Glucose Index (TyG) and HOMA-IR (Homeostatic model assessment)-IR were calculated by following formula :- Triglyceride Glucose Index (TyG) = Ln [Fasting Triglycerides (mg/dL) × Fasting Glucose (mg/dL)]/2. HOMA-IR = Fasting Insulin (µIU/ml) × Fasting Glucose (mmol/l)/22.51. Results: There is a significant mean difference in BMI, Fasting insulin, fasting blood glucose, triglyceride, HDLC, triglyceride index and HOMA-IR between prediabetes and type 2 diabetes group.There is a significant positive correlation of TyG with HOMA-IR in prediabetes group and type 2 diabetes mellitus group. ROC curve Test the TyG value to predict type 2 diabetes mellitus. TyG index exhibits higher AUC 0.94 with CI (0.88-1.00). Conclusion: The study shows significant differences in key metabolic markers between prediabetes and type 2 diabetes mellitus, with a strong positive correlation between TyG index and insulin resistance in both groups. JCMCTA 2025 ; 36 (2) : 107-111